Ontogenesis of opercular deformities in gilthead sea bream Sparus aurata: a histological description. Issue 5 (15th September 2017) - Thuong, N. P.; Verstraeten, B.; Kegel, B. D.; Christiaens, J.; Wolf, T. D.; Sorgeloos, P.; Bonte, D.; Adriaens, D.
Abstract : The aim of this study was to characterize histological changes during opercular osteogenesis in farmed gilthead sea bream Sparus aurata larvae from 7 to 69 days post hatching (dph) and compare normal osteogenesis with that of deformed opercles. Mild opercular deformities were first detected in 19 dph larvae by folding of the opercle's distal edge into the gill chamber. Here, the variation in the phenotype and the irregular bone structure at the curled part of the opercles is described and compared with the histology of normal opercles. Results indicated that deformed opercles still undergo bone growth with the addition of new matrix by osteoblasts at the opercular surface, especially at its edges. No significant difference was found in bone thickness between deformed and normal opercles. In addition to differences in bone architecture, differences in collagen fibre thickness between normal and deformed opercles were also found.